Impacts of community health insurance schemes on health care provision in rural Tanzania - John M. Msuya; Johannes P. Jütting; Abay Asfaw (University of Bonn, Center for Development Research (ZEF), 2004)
In 1996 the Tanzanian government initiated community health insurance schemes to improve the access to health care and to protect people against the financial cost of illness in an environment with shrinking budgets for the health sector. This study aims to evaluate the role of the community health funds (CHF) in lowering the barriers to access health care. Three important results emerge from this study: First, the results show that income is amongst the most important factors determining household participation in the schemes. This means that despite exemption mechanisms, the poorest of the poor within the society are not reached as they can not afford to pay regular insurance premiums. Secondly, though we find no significant differences between members and non-members in the overall amount of health expenditure and in the use of preventive measures, sick individuals in member households were 15 percentage points more likely to get treatment than those in non-member households. Hence, being insured leads to an increase in the effective demand for health care. Third, the analysis reveals that members of the CHF are better financially protected against health shocks than non members. The result of this work provides further evidence of the important role that micro insurance schemes can play in the risk management of people in developing countries.
Keywords: 330; Health Economics and Policy; Gesundheitsversorgung; Gesetzliche Krankenversicherung; Gemeinde; Ländlicher Raum; Tansania; Mikrofinanzierung